Kauman: A Contemporary Little Mecca in Indonesia - Jati, Wasisto Raharjo (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
The concept of "Little Meccas" in Indonesia refers to settlements designed to foster a symbolic connection between  local communities and Mecca, the holiest city in Islam. This paper delves into Kauman, a historic enclave in Yogyakarta that has served as a vibrant center of Islamic learning since the Sultanate era. By focusing on Kauman Yogyakarta, this study examines its transformation from a small residential area to a larger community that ultimately inspired the birth of Muhammadiyah, a prominent reformist Islamic movement. The paper explores the historical connections between Kauman and the Middle East, particularly the influence of pan-Islamism and reformist Islamic movements. This influence is further highlighted by the presence of architectural elements reflecting Middle Eastern styles. Notably, Kauman's pedestrianized zones prioritize tranquility for students pursuing Islamic studies in prayer halls (suraus or langgars). This emphasis on quietude underscores the importance placed on Arabic-style Islamic education within the enclave. In conclusion, this study investigates the ongoing influence of the Middle East on Islamic practices and education in Kauman. It sheds light on the concept of "Little Meccas" as a historical and cultural phenomenon in Indonesia.